The Effect of Specific Balance Training Exercises for Preventing Falls among Elderly Women (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2012)
All European countries are experiencing significant ageing of the population. As the lifespan of the population increases, so does the prevalence of falls. Falls in older adults are a major public health concern and a main cause of morbidity and disability. More than one-third of persons 65 years of age or older fall each year, and in half of such cases the falls are recurrent. It is very important to maintain physical activity and independence in daily activities in elderly persons as well as to apply appropriate preventive means as soon as possible. Various interventions may be used to promote health, enhance quality life and reduce falls in elderly people: exercises, home modifications, appropriate footwear and walking aids. The purpose of this study was to determine the effect of specific balance training exercises for preventing falls among elderly women. Twenty eight women aged 55–75 years participated in the study. The subjects were randomly divided into two groups: exercise (n = 14, mean age 67.9 ± 6.13 years) and control (n = 14, mean age 68.9 ± 5.31). Exercise group women performed specific – Cawthorne-Cooksey balance training exercises for 4 weeks, 5 times a week. Cawthorne-Cooksey exercises consisted of moving head in sitting and standing positions with eyes open or closed, exercises on a balance platform, and walking around. One training session lasted for 30-35 minutes. No exercise was performed in the control group. Static and dynamic balance was assessed using the Berg Balance Scale, Functional Reach Test, and Tinetti Balance Scale, walking speed was assessed using Timed Up and Go Test. Risk for falls was assessed using Desmond Fall Risk Questionnaire [4]. Subjects were evaluated twice: before and after applying exercise program. More than 50% of women have had a fall in the past years, difficulty walking in the dark or on uneven surfaces, they have experienced loss of balance or a light-headed feeling standing up, and they could not walk a straight line. Only 29% of subjects participated in a regular exercise programme. The results of Berg Balance Scale, Functional Reach Test, Tinetti Balance Scale, Timed Up and Go Test did not differ between groups before applying specific exercise program. Specific exercises significantly improved patients’ static and dynamic balance, reach functions and walking speed, while in the control group the results of all performed tests had tendency to decline. Specific Cawthorne-Cooksey balance training exercises are effective (p < 0.05) in improving balance and preventing falls in elderly women.Keywords: falls, elderly age, balance, risk of falls.